Government Discretion In Covid-19 Emergency Situations And Its Potential For Violating The General Principles Of Good Governance - simarmata, gledi; Amelia, Saskyani; Ramadhani, Nandita; Tarihoran, Salwa Azzahra (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Discretion is an authority given to public officials to act independently in taking actions that are not regulated by laws and regulations. Such a situation has the potential for abuse of power, because at the same time to carry out public policy, so that the intention arises to achieve personal or group benefits. So that officials are not arbitrary in performing their duties, the use of discretion has special conditions. However, various problems related to the use of discretion that are contrary to the applicable legal system are still found in several government organizations. The discussion examined in this journal is related to discretion and responsibility by government officials in carrying out duties in emergency situations and its limits against the law which has an influence on administrative law and criminal law in implementing duties in emergency situations. The purpose of this article is to explain the stipulations in the application of administrative discretion and some of the liabilities associated with legal deviations. As a state of law, the principle of legality alone is not sufficient to ensure legal certainty and prevent abuse of power by the government. Discretion emerges as an alternative to fill the weaknesses and shortcomings in the application of the principle of legality. The General Principles of Good Governance (AUPB) are guidelines for the use of discretion. The method of approach used in this article is normative juridical, which aims to understand the discretion and responsibility of government officials in carrying out duties in emergency situations and on the limits of actions facing the law resulting in administrative law and criminal law in carrying out duties in emergency situations. The results show that although discretion is necessary, its implementation must be in accordance with Law Number 30 of 2014 in order to stay within the legal corridors. It was found that overlapping authorities and weak supervision in the implementation of discretion during the pandemic have the potential to cause violations of the law. Therefore, more detailed implementing regulations are needed as well as strengthening the understanding of AUPB for public officials to prevent abuse and ensure accountability.